Example

# Gear Configuration 1

Here,

*f = 2*

*a = 1*

*l = 4*

from which, we get

(1)\begin{align} \frac {\omega_{4/1}}{\omega_{2/1}}& =\frac {\omega_4-\omega_1}{\omega_2-\omega_1}\\ \end{align}

(2)
\begin{split} \frac {\omega_{4/1}}{\omega_{2/1}}& =\left(\frac {-N_2}{N_3}\right)\left(\frac {N_3}{N_4}\right)\\ & =\left(\frac {-N_2}{N_4}\right)\\ \end{split}

therefore from (1) and the expression above, we get

(3)\begin{align} \omega_4 & =\left(\frac {-N_2}{N_4}\right)\left(\omega_2 - \omega_1\right) + \omega_1\\ \end{align}

This is the angular velocity of the *Ring gear* in terms of the angular velocity of the *Arm* and the angular velocity of the *Sun gear* for the configuration shown.

Help | Terms of Service | Privacy | Report a bug | Flag as objectionable

Powered by Wikidot.com

page revision: 2, last edited: 08 Sep 2010 19:03